2002
DOI: 10.1007/s00204-002-0350-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic acid in combination with a chelator ameliorates lead-induced peroxidative damages in rat kidney

Abstract: The deleterious effect of lead has been attributed to lead-induced oxidative stress with the consequence of lipid peroxidation. The present study was designed to investigate the combined effect of DL-alpha-lipoic acid (LA) and meso-2,3-dimercaptosuccinic acid (DMSA) on lead-induced peroxidative damages in rat kidney. The increase in peroxidated lipids in lead-poisoned rats was accompanied by alterations in antioxidant defence systems. Lead acetate (Pb, 0.2%) was administered in drinking water for 5 weeks to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 39 publications
2
17
2
Order By: Relevance
“…Monterio et al (1985) showed that individuals exposed to lead have increased antioxidant defenses (SOD and GPX), and they found a nonlinear relationship between Pb-B and SOD. Recently Sivaprasad et al (2002) also reported a decrease in the concentrations of reduced glutathione and an increase in the levels of oxidized glutathione and MDA in lead acetate treated rats. Both experimental and clinical studies reported for years that lead exposure in the acceptable intoxication ranges can cause oxidative damage.…”
Section: Discussionmentioning
confidence: 94%
“…Monterio et al (1985) showed that individuals exposed to lead have increased antioxidant defenses (SOD and GPX), and they found a nonlinear relationship between Pb-B and SOD. Recently Sivaprasad et al (2002) also reported a decrease in the concentrations of reduced glutathione and an increase in the levels of oxidized glutathione and MDA in lead acetate treated rats. Both experimental and clinical studies reported for years that lead exposure in the acceptable intoxication ranges can cause oxidative damage.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that Pb causes oxidative stress by generating ROS in different organs [51][52][53][54][55]. Sub-chronic low Pb exposure produces nephrotoxicity in vivo and in vitro [36], as well as infertility [56] in rodents.…”
mentioning
confidence: 99%
“…Furthermore, studies have clearly demonstrated that depletion of GSH leads to the cellular damage as well as colonic injuries. GSH is one of the first lines of oxidative defense mechanisms against free radicals (41), and can prevent ROS oxidative injuries (42,43).…”
Section: Discussionmentioning
confidence: 99%